Is related party transactions linked to accounting comparability? Evidence from emerging market - Phung Anh Thu; Pham Quang Huy; Le Huu Tuan Anh (Cogent Business & Management, 2023)
This paper aims to evaluate the relationship between related party transaction (RPT) and accounting comparability (AIC). In this study, the authors use a generalized method of moments (GMM) method to assess the RPT-AIC association by using a sample of 441 non-financial companies in Vietnam for the period 2015-2019. Using the monetary scale to measure the size of the kinds of RPT transactions, the authors find evidence for a positive relation between RPT and AIC. Besides, our results are confirmed through different robustness tests by applying different ways of measurement for RPT and AIC. This study provides valuable empirical evidence about the relationship between RPT and AIC through the research context of an emerging market like Vietnam. This is the first study to diversify the research context in the developing country to answer whether the impact of RPT on business is context-based or global.
Keywords: 650; emerging market; accounting comparability; related party transactons; RPT purchases; RPT sales